Sensory Evaluation of Carbonated Coconut Water Fortified with Nutmeg Juice - Sophia Grace Sipahelut (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Old coconut water is underutilized and often ends up as waste. However, old coconut water contains macro and micro nutrients that provide health benefits. Therefore, efforts are needed to develop old coconut water, one of which is carbonated drinks. The taste of old coconut water tends to be rather bland, so formulation innovation is needed by adding other ingredients to improve the taste and consumer acceptance, such as nutmeg juice. The purpose of this study was to study the sensory characteristics of carbonated drinks using different proportions of old coconut water and nutmeg juice. The research method used was an experimental method using the ratio of coconut water and nutmeg juice (90:10; 80:20; 70:30; 60:40). Sensory characteristic testing was carried out by 30 semi-trained panelists, including tests of taste, aroma, color, texture, and sparkle effect. The results of the study showed that carbonated drinks with the ratio of old coconut water and nutmeg juice affected the sensory characteristics of carbonated drinks. The sensory characteristics of the resulting carbonated drinks included: taste characteristics 2.85-4.45 (slightly nutmeg flavor to nutmeg flavor); aroma characteristics 2.95-4.55 (slightly nutmeg flavor to nutmeg flavor); color characteristics 2.30-3.85 (pale yellow to brownish yellow); texture characteristics; 2.85-4.60 (less thick to thick); sparkle effect 3.70-4.25 (quite noticeable sparkle effect to noticeable sparkle effect).